Upaya Perlindungan Hukum Terhadap Kekerasan Seksual atau Penganiayaan Anak Dibawah Umur - Sagita, Anisa Nur (UM Purwokerto Press, 2024)
Cases of sexual violence in children are so alarming that making parents who have young children become more vigilant and fearful of the safety of their children. This article discusses the importance of interpersonal communication between parents and children, especially those aged early to give an understanding of self-protection. Good communication is essentially applied between parents and children in order to generate a positive relationship. The communication must be built starting from early childhood, it is intended that the creation of a good relationship between parents and children to create a harmonious relationship. Families who have problems with family characteristics that are not reasonable and have children who need care the family problems that must be fixed first. Children who do not have a father or mother becomes the main to be considered by the government. Families who have the ability to raise children well and have sufficient knowledge to equip and protect children from violence and child abuse then can the communication between parents and children is necessary, through sex education for children, expressing themselves honestly, communication Interpersonal Harmonious, an example by using good language and motivation to become independent.